APPLICATION OF TAXATION ON TRANSACTIONS E-COMMERCE ON THE MARKETPLACE PLATFORM - Leonardo, Posma (Universitas Pendidikan Indonesia, 2020)
This study is based on the problem of the development of e-commerce transactions that do not necessarily boost state revenues from the taxation sector. This study aims to analyze the application of SE-62 / PJ / 2013 dated 27 December 2013 concerning Affirmation of Taxation Terms on E-Commerce Transactions at PT Bukalapak.com and provide recommendations to PT Bukalapak.com related to the taxation aspect of e-commerce transactions. This study uses a mixed-method approach. The object of the research is PT Bukalapak.com with the Tax Division as a unit of analysis. The conclusion of the study is that PT Bukalapak.com does not implement or apply specific provisions for users of the Bukalapak application, this refers to the taxation system carried out in Indonesia, namely self assessment. Lack of tax knowledge on taxation obligations causes less success in maximizing tax payments on e-commerce transactions